2011
DOI: 10.1371/journal.pone.0024453
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Screen Time and Physical Activity among Spanish Adolescents

Abstract: BackgroundExcessive time in front of a single or several screens could explain a displacement of physical activity. The present study aimed at determining whether screen-time is associated with a reduced level of moderate to vigorous physical activity (MVPA) in Spanish adolescents living in favorable environmental conditions.Methodology/Principal FindingsA multi-stage stratified random sampling method was used to select 3503 adolescents (12–18 years old) from the school population of Gran Canaria, Spain. MVPA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
55
1
13

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 64 publications
(67 reference statements)
13
55
1
13
Order By: Relevance
“…Of greater concern is that those who accumulated more screen time engaged in significantly fewer MET hours of physical activity per week. This trend has been reported before 27 and highlights the existence of a sedentary inactive cohort of youth who may be at risk of developing health problems, including the metabolic syndrome. 30,31 An objective of this study was to determine the percentage of children in sixth class in Dublin who have access to electronic game consoles, including AVG consoles.…”
Section: Discussionsupporting
confidence: 60%
“…Of greater concern is that those who accumulated more screen time engaged in significantly fewer MET hours of physical activity per week. This trend has been reported before 27 and highlights the existence of a sedentary inactive cohort of youth who may be at risk of developing health problems, including the metabolic syndrome. 30,31 An objective of this study was to determine the percentage of children in sixth class in Dublin who have access to electronic game consoles, including AVG consoles.…”
Section: Discussionsupporting
confidence: 60%
“…Our findings are consistent with published studies from other countries. [39][40][41][42][43] For example, a crosssectional study 43 of Canadian adolescents found no association between reported physical activity levels and the amount of time spent in screen-based sedentary behaviors. In addition, a study 40 of European youth also found no association between accelerometer-measured MVPA and the amount of time spent watching TV and showed that TV viewing and physical activity may be differently associated with adiposity and metabolic risk.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have examined problematic Internet use and its impact on children Hawi, 2012;Tsitsika et al, 2014). Also, screen media use negatively affects children's physical health (Colley et al, 2013;Salmon et al, 2011;Serrano-Sanchez et al, 2011;Strasburger et al, 2010;Tremblay et al, 2010), in particular obesity (Atkin et al, 2014;Laurson et al, 2008;Must et al, 2007;Stamatakis et al, 2013), diabetes (Dunstan et al, 2010;Goldfield et al, 2013), high blood pressure (Martinez-Gomez et al, 2009), higher BMI (Arcan et al, 2013;Fulton et al, 2009;Jackson et al, 2011), cardiometabolic and heart diseases (Altenburg et al, 2012;Berentzen et al, 2014;Grøntved et al, 2014;Mark and Janssen, 2008), and sleep irregularity (Thompson and Christakis, 2005).…”
Section: Introductionmentioning
confidence: 99%